A Review of the Emergence of Muslim Organizations in Yorubaland, Nigeria - Yisa Olorunda Balogun (International Journal of Religion, Humanity and Cultural Heritage, 2025)
Muslim organizations in Yorubaland consist of the ones that were formed before, during and after the colonial era. They were formed in emulation of the practice of the formation of the organizations before the advent of Islam in the study area. The major aims and objectives of the formation of the organizations were unity and to speak with one voice on Islamic affairs. The paper examines age grade and guild. Most of the early Muslim Organizations bore Yoruba names and were the precursors to other Muslim Organizations that emerged later. It discusses the League of Imams and Alfas, and the Ansar-Ud-Deen Society. It also discusses the advantages of Muslim organizations to include the formation of a group of Muslims of like minds as a single body and construction of different structures for the benefits of members. Its disadvantages consist lack of proper accountability of the leaders and mixture of non-Islamic cultures and civilization to Islam. Findings reveal that fighting for supremacy, political appointments and acquisition of national cake between the League of Imams and Alfas, and Ansar-Ud-Deen Society, especially in Ekiti State, Nigeria. The paper concludes by stating that most of the Muslims of Yorubaland now belong to one Muslim organization or more.